URGENSI MATA KULIAH HUKUM BISNIS DALAM MENINGKATKAN LITERASI HUKUM MAHASISWA PPKN IPI GARUT DI ERA DIGITAL - Cahya Lesmana; Prima Melati; Barkah Juliansyah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the urgency of the Business Law course in improving legal literacy among students of the Civic Education Study Program in the digital era. This research uses a descriptive qualitative approach with data collection techniques through in-depth interviews with 10 students who have taken the Business Law course, observation, and documentation. The results show that the Business Law course plays an important role in enhancing students’ understanding of rights and obligations in economic activities, particularly in digital transactions. Students become more cautious in online transactions and gain better understanding of consumer protection, business agreements, and business ethics. In addition, the learning process also improves students’ legal awareness, although some difficulties remain in understanding complex legal terminology. Therefore, the Business Law course significantly contributes to improving students’ legal literacy in the digital era.